Formation of specialists competitiveness in industry of physical culture and sport in higher educational establishments of non-state pattern of ownership - Zavatska L.A; Sotnik J.H; Ilkiv O.S (Kharkov National Pedagogical University, 2011)
The terms of forming future specialists competitiveness of physical culture and sport are considered. The analysis of publications by authors row, which investigated this problem in higher educational establishments of different patterns of ownership, forming model of graduating students competitiveness is given. It is set that the competitiveness of graduating students depends on objective and subjective factors, modern demand at the market of labour, potential possibilities of higher educational establishments, introduction of the additional individualized and traditional components of process.